Dataset associated with 'Biomimetic curvature and tension-driven membrane fusion by silica nanoparticles’ - Arribas Perez, Marcos (University of Leeds, 2021)
Experimental data obtained from FRET spectroscopy and confocal microscopy imaging of lipid vesicles interacting with silica nanoparticles. Experimental set up and data processing and analysis described in the publication in Langmuir. Confocal microscopy movies of giant unilamellar vesicles undergoing fusion upon interaction with silica nanoparticles.
Keywords: FOS: Biological sciences; FOS: Chemical sciences; Biophysics